The Effect Of Exposure Index Variations On Subjective Quality Assessment On Lumbosacral Examination - Putri Rahmawanti; Muhammad Irsal; Gando Sari (Jurnal Teori dan Aplikasi Fisika, 2022)
Exposure index (EI) is an indicator of dose used to determine overexposed, optimal and underexposed images so that this study discusses the effect of EI variations on subjective image quality assessment on lumbosacral examination. This research uses descriptive quantitative method by filling out questionnaires and calculating the radiation output dose. Then to draw conclusions, perform a visual grading analysis (VGA) statistical test using the one-way ANOVA test. The results obtained by varying the EI for AP projections of 2.99 (overexposed), 2.79 (optimal), and 2.33 (underexposed) then for Lateral projections of 2.91 (overexposed), 2.76 (optimal), and 2.46 (underexposed). Furthermore, the dose calculation using the radiation output equation produces 3.158 mGy (overexposed), 0.78 mGy (optimal) and 0.57 mGy (underexposed) for the AP projection while for the lateral projection it produces a radiation dose of 3.61 mGy (overexposed), 1.52 mGy (optimal). , and 0.78 mGy (underexposed). Then to get a conclusion, VGA test was carried out using ANOVA testing, the data generated after performing ANOVA tests on AP and lateral projections showed results of 0.87 and 0.612. Based on the results of the ANOVA that has been carried out, the conclusion is that all respondents have the same assessment of the quality of the lumbosacral image that the image with the overexposed EI indicator is a better image than the image with the optimal and underexposed EI indicator.